2011
DOI: 10.1002/art.30612
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced secretion of leukocyte-associated immunoglobulin-like receptor 2 (LAIR-2) and soluble LAIR-1 in rheumatoid arthritis: LAIR-2 is a more efficient antagonist of the LAIR-1-collagen inhibitory interaction than is soluble LAIR-1

Abstract: Objective. Human leukocyte-associated immunoglobulin-like receptor 1 (hLAIR-1) is an immune inhibitory receptor for collagen that is expressed on most immune cells. We previously showed that the LAIR-1-collagen interaction could be antagonized by the secreted homolog hLAIR-2, which can be detected in the synovial fluid of rheumatoid arthritis (RA) patients. In addition, the extracellular part of hLAIR-1 is a putative antagonist upon shedding from the cell membrane. The purpose of this study was to determine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
61
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(73 citation statements)
references
References 23 publications
12
61
0
Order By: Relevance
“…Although α2β1 integrins bind collagens and may function as C1q receptors, they lack an intracellular ITIM domain (1,25). LAIR-2, which has been shown to be increased in certain autoimmune settings (17), also bound C1q and blocked C1q effects on cell differentiation and activation. Thus, LAIR-2 may be a key physiological regulator of C1q and LAIR-1 interactions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although α2β1 integrins bind collagens and may function as C1q receptors, they lack an intracellular ITIM domain (1,25). LAIR-2, which has been shown to be increased in certain autoimmune settings (17), also bound C1q and blocked C1q effects on cell differentiation and activation. Thus, LAIR-2 may be a key physiological regulator of C1q and LAIR-1 interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence that disrupted LAIR-1-mediated immune silencing leads to a loss of self-tolerance in disease settings includes deficient LAIR-1 expression on pDCs and B cells in SLE, correlating with increased IFN-α production and defective regulation of B-cell antibody secretion, respectively, and increased levels of LAIR-2 (a soluble LAIR-1 inhibitor) in rheumatoid arthritis (14,16,17). Based on the increasingly evident contribution of LAIR-1 and C1q to immune homeostasis, the extent of shared activities of LAIR-1 and C1q, and the presence of numerous potential LAIR binding sites on the CLR of C1q, we hypothesized that LAIR-1 binds C1q to suppress immune cell activity.…”
mentioning
confidence: 99%
“…(Supplementary Figure 1) Included in the top 5% expressed genes were several genes with previously reported association to inflammation and/ or Rheumatic or Osteoarthritis; such as LAIR 1, TMSB4X, CCR6, IL18 and IL10 [2,[14][15][16][17].…”
Section: Resultsmentioning
confidence: 99%
“…These reported genes include LAIR1, TMSB4X, CCR6, IL18, IL10 [2,[14][15][16][17]. LAIRI is the highest expressed gene among all the samples.…”
Section: Discussionmentioning
confidence: 99%
“…Ligation of LAIR-1 generates a threshold for activation of various cellular functions [6]. Collagens serve as ligands for LAIR-1 [7,8], and we recently found that in particular dimeric recombinant LAIR proteins have a high affinity for collagen [9]. Recently, Son et al [10] reported C1q as ligand for LAIR-1 on dendritic cells.…”
Section: Introductionmentioning
confidence: 99%